Globalization and Wage Convergence: Mexico and the United States - Davide Gandolfi; Timothy J. Halliday; Raymond Robertson (Institute for the Study of Labor (IZA), 2014)
Neoclassical trade theory suggests that factor price convergence should follow increased commercial integration. Rising commercial integration and foreign direct investment followed the 1994 North American Free Trade Agreement between the United States and Mexico. This paper evaluates the degree of wage convergence between Mexico and the United States between 1988 and 2011. We apply a synthetic panel approach to employment survey data and a more descriptive approach to Census data from Mexico and the US. First, we find no evidence of long-run wage convergence among cohorts characterized by low migration propensities although this was, in part, due to large macroeconomic shocks. On the other hand, we do find some evidence of convergence for workers with high migration propensities. Finally, we find evidence of convergence in the border of Mexico vis-à-vis its interior in the 1990s but this was reversed in the 2000s.
Keywords: F15; F16; J31; F22; 330; migration; labor-market integration; factor price equalization